The Investigation of Thickness-Dependent Mono-Fractal, Optical and Optoelectronics Properties of Sputtered Silver Thin Film for Silicon Solar Cell - Escrig-Murua, J; Kumar, C (Elsevier Ltd, 2024)
Here we report, the room temperature deposition of silver (Ag) thin films on silicon, glass and silicon solar cell substrates by magnetron sputtering. The effect of thickness on the deposited thin films and their morphological, fractal, optical and solar cell parameters have been extensively investigated. AFM results show that the Ag thin films are composed of different-size of nano-grains and the grain size increases with increasing thickness. Mono-fractal parameters, namely fractal dimension (Df) and Hurst exponent (H), were determined from the power spectral density function. X-ray photoelectron spectroscopy studies indicate that the deposited samples exhibit the presence of oxidation state of Ag (0) in thin films, confirming the stable structure. The optical analysis shows that the transmittance of the deposited thin films decreases with increasing thickness, on the other hand, the silver thin film with thickness of 20 nm shows surface Plasmon resonance (SPR) at 436 nm. Current-voltage (I–V) curves were measured in dark and under illumination mode at standard testing conditions, i.e., 300K, 1000 W/m2 and 1.5 AM global using a solar simulator. These measurement studies indicate that thicknesses are effectively impacts on photovoltaic performance. The calculated values of change in solar efficiency (Δη) are 0.26, −0.20, −0.76 and −6.88 % for thin films with nominal thickness 0.5, 1, 2 and 20 nm respectively. © 2024 Elsevier Ltd